Comparison of 5‐year postoperative outcomes after Billroth I and Roux‐en‐Y reconstruction following distal gastrectomy for gastric cancer: Results from a multi‐institutional randomized controlled trial. Issue 1 (15th September 2020) - Kimura, Yutaka; Mikami, Jota; Yamasaki, Makoto; Hirao, Motohiro; Imamura, Hiroshi; Fujita, Junya; Takeno, Atsushi; Matsuyama, Jin; Kishi, Kentaro; Hirao, Takafumi; Fukunaga, Hiroki; Demura, Koichi; et al.
Abstract: Aim: We previously reported in a randomized controlled trial that Billroth I and Roux‐en‐Y reconstructions were generally equivalent regarding body weight change and nutritional status 1 year after distal gastrectomy for gastric cancer. We describe the long‐term follow‐up data 5 years after distal gastrectomy. Methods: We analyzed consecutive gastric cancer patients who were randomly assigned to undergo Billroth I or Roux‐en‐Y reconstruction after distal gastrectomy. We evaluated body weight change, nutritional status, late complications, quality of life (QOL) using the European Organization for Research and Treatment of Cancer Core QOL Questionnaire, and dysfunction using the Dysfunction After Upper Gastrointestinal Surgery for Cancer, 5 years after surgery. Results: A total of 228 patients (Billroth I = 105; Roux‐en‐Y = 123) were eligible for efficacy analyses in this study. Body weight loss 5 years after surgery did not differ significantly between the Billroth I and Roux‐en‐Y groups (10.0% ± 7.9% and 9.6% ± 8.4%, respectively; P = .70). There were no significant differences in other aspects of nutritional status between the two groups. Reflux esophagitis occurred in 19.0% of the patients in the Billroth I group vs 4.9% in the Roux‐en‐Y group ( P = .002). Regarding QOL, Billroth I was significantly inferior to Roux‐en‐Y on the diarrhea scale (Billroth I: 28.6, Roux‐en‐Y: 16.0; P = .047). Regarding dysfunction, no score differed significantly between the two groups. Conclusions: Billroth I and Roux‐en‐Y reconstructions were generally equivalent regarding body weight change, nutritional status, and QOL 5 years after distal gastrectomy, although Roux‐en‐Y more effectively prevented reflux esophagitis and diarrhea. Abstract : Billroth I and Roux‐en‐Y reconstructions were generally equivalent regarding body weight change, nutritional status, and quality of life 5 years after distal gastrectomy, excluding reflux esophagitis and diarrhea.